Improving Environmental Knowledge and Awareness Through Conservation Education Containing Religious Values in Prospective Biology Teacher - Djohar Maknun; Jajang Aisyul Muzakki; Ipin Aripin (Postgraduate, University of Mataram, 2025)
The purpose of this study is to describe efforts to improve environmental knowledge and awareness in prospective biology teacher students through a conservation education program containing religious values. This study uses a qualitative approach with a quasi-experimental method. Research data were collected through tests (quantitative data), questionnaires (qualitative). Qualitative data was analyzed using descriptive analytical techniques, while quantitative data was analyzed using inferential statistical techniques, specifically t-tests and N-gain analysis. Research interventions were carried out through the integration of religious values in conservation education through the ayatization/labelling approach, namely by quoting verses of the Qur'an that are relevant to the concept of conservation. The results of the study found that the implementation of conservation education containing religious values can improve environmental knowledge and awareness in prospective biology teacher students. The integration of religious values in conservation education builds a comprehensive understanding and provides a more binding moral encouragement so as to foster awareness and responsibility for the environment that is better than other approaches. The results of this study can be an alternative to an effective conservation education program so that it becomes a solution in the development of conservation education in Indonesia.